2021
DOI: 10.21203/rs.3.rs-596219/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chaotic Dynamics of a Tri-Topic Food Chain Model with Beddington-DeAngelis Functional Response in Presence of Fear Effect

Abstract: The most important fact in the field of theoretical ecology and evolutionary biology is the strategy of predation for predators and the avoidance of prey from predator attack. A lot of experimental works suggest that the reduction of prey depends on both direct predation and fear of predation. We explore the impact of fear effect and mutual interference into a three-species food chain model. In this manuscript, we have considered a tri-topic food web model with Beddington-DeAngelis functional response between … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…They found that fear could stabilize a predator-prey system by excluding population oscillations. Recently, Roy and Alam [7], Sk et al [8,9], Mondal et al [10], and others [11,12] have studied their model incorporating fear effect.…”
Section: Introductionmentioning
confidence: 99%
“…They found that fear could stabilize a predator-prey system by excluding population oscillations. Recently, Roy and Alam [7], Sk et al [8,9], Mondal et al [10], and others [11,12] have studied their model incorporating fear effect.…”
Section: Introductionmentioning
confidence: 99%